Pengaruh Kecemasan Dan Depresi Terhadap Self-Efficacy Ibu Menyusui Pada Masa Nifas: Literature Review - A. Sri Ulfi Nofriati (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2024)
Breast milk is the main need for newborn babies, and it is important to give it exclusively for up to six months or more. Not all mothers, after giving birth, can breastfeed their babies because the breastfeeding process is always associated with symptoms of postnatal anxiety and depression. For mothers with anxiety and depression, it can cause a decrease in self-efficacy when breastfeeding, resulting in an early cessation of breastfeeding. Therefore, the aim of this research is to determine the influence of anxiety and depression on the self-efficacy of breastfeeding mothers during the postpartum period. The research method is a literature review by collecting and reviewing 7 research journals via Google Scholar and ScienceDirect. The results obtained show that there is an influence between anxiety and depression on the self-efficacy of breastfeeding mothers during the postpartum period.